MRI evidence for commonality in the post-oral articulations of English vowels and liquids - Gick, Bryan; Min Kang, A.; Whalen, D.H. (Journal of phonetics, 2002)
One advantage of using articulatory gestures in models of speech production is that a single gesture can function as a component in a number of different traditional segments (e.g., the tongue tip constrictions for /t/, /d/, /n/ and /l/). Few such claims, however, have been made with reference to more dorsal tongue gestures such as those in American /r/ and /l/. The present paper tests a proposed connection between the pharyngeal components of English liquids and vowels. Midsagittal MRIs of the vocal tracts of three speakers of American English were collected during the production of all vowels in each subject's inventory, plus /r/ and /l/. Midsagittal distances between the tongue and opposing surfaces were measured at intervals along the length of the vocal tract, and the vocal tract was divided into regions: lower pharyngeal, upper pharyngeal, uvular and oral. Vowel shapes were subtracted point by point from /r/ and /l/, allowing a single RMS difference to be calculated within each region of the vocal tract. Results support the prediction that, at least in some dialects, a single postoral gesture is shared between /l/ and /c:/, and between /r/ and schwa.